PENGARUH TATA HIJAU TERHADAP SUHU DAN KELEMBABAN RELATIF UDARA PADA BALAI BESAR PENGEMBANGAN MEKANISASI PERTANIAN, SERPONG - Femy, .; Budiarti, Tati; Nasrullah, Nizar (Jurnal Lanskap Indonesia, 2014)
Green Open Space on office area essential to be considered to create a comfortable environment. Greenery in BBP MEKTAN need to be improved to increase the climatological comfort, beside built area around. The Study aimed to asses the effect of canopy shape, distance from tree, and tree distance from building. This study also asses the relation between temperature and RH of green open space, and planning for BPP MEKTAN greenery for climatological comfort. The observation was conducted in the area of BBP MEKTAN. The observation was conducted from February to May 2013 in BPP MEKTAN. The Analysis of temperature and humidity was performed by varian analysis and middle value test. The result of this study showed that the shape of canopy affect the temperature and humidity, the crown around and round open decrease the average temperature about 2C and increase humidityabout 5%.he farther the distance from the tree, then the effect of a decrease in temperature and increase in humidity are decreasing. The closer the trees from the buildings and the wider canopy cover, result on a decreasing in temperature and an increasing in RH indoor Cover area of open green space associated with the temperature and humidity, the total area of open green space relationship with temperature. Planning of green open space in BBP MEKTAN was based on the results of previous study 1 and 2, that is conducted by addition of vegetation that provides shade effect in areas close to buildings, roads, and parking areas.